Convergence of Bar and Cry1Ac Mutant Genes in Soybean Confers Synergistic Resistance to Herbicide and Lepidopteran Insects - Nguyen, Tien Dung; La, Van Hien; Nguyen, Van Duy; Bui, Tri Thuc; Nguyen, Thi Tinh; Je, Yeon Ho; Chung, Young Soo; Ngo, Xuan Binh (Frontiers in Plant Science, 2021)
The yield of soybean, a globally important crop species, may be substantially reduced by insects and weeds. Despite the success of transgenic soybean in terms of Bt and herbicide tolerance, however, unforeseen mitigated performances have been inspected due to climate changes that favor the emergence of insect resistance. Therefore, there is a need to develop a biotech soybean with elaborated gene stacking to improve insect and herbicide tolerance in the field. In this study, new gene stacking soybean events such as bar and cry1Ac mutant 2 (M#2) is being developed in Vietnamese soybean under field condition. Five transgenic plants were extensively studied in the herbicide effects, gene expression patterns, and insect mortality across generations. The increase in the expression of bar gene by 100% in the leaves of putative transgenic plants was a determinant of herbicide tolerance. In an insect bioassay, the cry1Ac-M#2 protein tested yielded higher than expected larval mortality (86%), reflecting larval weight gain and weight of leaf consumed were less in the T1 generation. Similarly, in the field tests, the expression of cry1Ac-M#2 in the transgenic soybean lines was relatively stable from T0 to T3 generations that corresponded to a large reduction in the rate of leaves and pods damage caused by Lamprosema indicata and Helicoverpa armigera. The transgenic lines converged two genes, producing a soybean phenotype that was resistant to herbicide and lepidopteran insects. Furthermore, the expression of cry1Ac-M#2 was dominant in the T1 generation leading to exhibit better phenotypic traits. These results underscore the great potential of combining bar and cry1Ac mutation genes in transgenic soybean as pursuant of ensuring resistance to herbicide and lepidopteran insects.